The dog who danced [large type] - Wilson, Susan, 1951- (Thorndike Press large print basic series., 2012)
Leaning on her beloved Sheltie after a lifetime of painful losses, Justine Meade struggles with a difficult separation when she returns to her childhood home after a twenty-year absence and encounters an estranged couple torn by the loss of their daughter.